Guideline for teaching pre-hospital life support. Consensus for the project of training and research in life support. Cienfuegos 2018 - Olga Lidia Sosa Rodríguez; Juan Ulises Castillo Sanz; Bárbara Hilaria Padrón Novales; Fernando Grondona Torres; Lázaro Águila Trujillo; Elier Carrera González; Grupo Fiaved-Avipreh (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: In the pre hospital scenario mortality due to emergencies is high, mainly because episodes are produced before arriving to the health system. Health personnel should be trained for facing these emergencies in this context. The project for training and researching in life support in emergencies and disasters nay be an academic framework to achieve it. Objective: to update the Project, guidelines and teaching strategy for training life support before emergencies in pre hospital emergencies. Method: qualitative study which had as a starting point the development of a National Workshop with 8 experts and 6 key informers, on July 10th and 11th in Cienfuegos. Besides documentary review, there were applied the techniques of brainstorming, nominal group, semi structured questionnaire. Results: the elements proposed for teaching pre-hospital life support, in under graduate and postgraduate courses were the following: objectives, didactical elements, teaching strategy, content, scope, skills to be developed, future research and areas of inter institutional collaboration. It was defined that the structure of a course model for teaching the topic and the main considerations for its execution. Conclusion: academic proposals for life support contain basic elements for training health professionals and students to provide medical assistance at site and in institutions of firs level of health.